3rd AeU Convocation - Asia e University, AeU (AeU, 2013)
The 3rd AeU Convocation ceremony was held on Sunday, 21st April 2013 at Dewan Tunku Canselor, Universiti Malaya, Kuala Lumpur.This ceremony marks another milestone in the history of the University.